Pitfalls and value of organ specific approach in evaluating indeterminate lesions detected on CT in colorectal cancer by [F18] FDG PET/CT. (2020) - Marashdeh, Wael M.; Al-Mugbel, Kusai M.; Alebbini, Mohanad Mutasem; Tashtoush, Amr Ghassan; Alghzawi, Ahmad Abdalmajeed; Al-Omari, Ma'moon H.; Alshari, Osama M.
Abstract: Objective: The objective of this study is to evaluate the value of FDG PET/CT for different involved organs showing Indeterminate/ equivocal / suspicious lesions detected on IV contrasted CT during surveillance follow up for colorectal cancer. Materials and methods: A total of 67 patients with colorectal cancer how are on regular surveillance follow up by IV contrasted CT scans revealing indeterminate lesions were studied. Subsequent FDG PET/CT evaluation was performed as a problem solving modality. PET/CT results were statistically characterized when compared to biopsy results or to follow/up results. Also Statistical parameters were calculated for each organ involved. The evaluation of all CT indeterminate lesions by FDG PET/CT showed overall sensitivity of 93%, Specificity of 81%, Negative predictive value of 94%, Positive predictive value 80% and accuracy of 87%. However in an organ specific approach the highest accuracy was for lymph nodes with results showing a 100% accuracy and the lowest accuracy was for local disease at a value of 80%. Probable explanations for the falsely characterized lesions resulting in the pitfalls seen and in the imperfect accuracy were provided. Conclusion: Study shows that FDG PET/CT is an excellent tool in characterizing CT indeterminate lesions during surveillance of colorectal cancer, However different organs showed variable accuracy results with the highest accuracy for our study was for lymph node status (100%) and the lowest accuracy being for local disease at the original site of primary tumor (80%).